1996
DOI: 10.1192/bjp.169.2.172
|View full text |Cite
|
Sign up to set email alerts
|

The Entry of Mentally Disordered People to the Criminal Justice System

Abstract: Both police and courts are well aware of the inappropriateness of custody for acutely ill people and efforts are made to divert such people out of the CJS. Persistent petty offenders are often being recycled from the street to police station to court and back to the street without the benefit of care. A dedicated facility is recommended in central London to meet this need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 4 publications
3
39
0
3
Order By: Relevance
“…As far as we are aware, this is the first study to use this method and procedure in this setting. Previous studies carried out among police custody detainees have relied on observational data 10 or pre-selected subgroups. 11,22,23 This paper considers the ability of standard police screening procedures to identify detainees with mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we are aware, this is the first study to use this method and procedure in this setting. Previous studies carried out among police custody detainees have relied on observational data 10 or pre-selected subgroups. 11,22,23 This paper considers the ability of standard police screening procedures to identify detainees with mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Keyes et al (1995) suggested that 1.9% of those passing through one central London station presented with overt symptoms of mental illness. A report to the Home Office (Robertson et al, 1995) shows that 2.7% of those admitted to custody suites in London had some form of mental illness and 1.4% demonstrated symptoms of a serious nature. Similar and higher levels have been found outside London, with serious psychiatric disorder in 6.6% of 1460 held in custody overnight (Shaw et al, 1999).…”
Section: At the Police Stationmentioning
confidence: 99%
“…These findings have been supported in a range of studies which demonstrate that: the mentally ill are more likely to come into contact with the police, have a higher arrest rate, are at a greater risk of entering custody rather being granted bail and are more likely to be arrested for relatively minor offences. (Teplin (1984), Pearson and Gibb (1995), and Robertson (1988)). …”
Section: Introductionmentioning
confidence: 99%
“…The increased contact outlined above has exacerbated some of these difficulties. As Robertson et al (1995) argue the police role is a very difficult and at times frustrating one. The major police function is clearly to detect crime and bring offenders before the Courts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation